Antiarrhythmic properties of ranolazine: inhibition of atrial fibrillation associated TASK-1 potassium channels - Ratte, Antonius; Wiedmann, Felix Tobias; Kraft, Manuel; Katus, Hugo; Schmidt, Constanze (Frontiers in pharmacology, 2019)
Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and one of the major causes of cardiovascular morbidity and mortality. Despite good progress within the past years, safe and effective treatment of AF remains an unmet clinical need. The anti-anginal agent ranolazine has been shown to exhibit antiarrhythmic properties by mainly late INa and IKr blockade. This results in prolongation of the atrial action potential duration (APD) and effective refractory period (ERP) with lower effect on ventricular electrophysiology. Furthermore, ranolazine has been shown to be effective in the treatment of AF. TASK-1 is a two-pore domain potassium (K2P) channel that shows nearly atrial specific expression within the human heart and has been found to be upregulated in AF, resulting in shortening the atrial APD in patients suffering from AF. We hypothesized that inhibition TASK-1 contributes to the observed electrophysiological and clinical effects of ranolazine. Methods: We used Xenopus laevis oocytes and CHO-cells as heterologous expression systems for the study of TASK-1 inhibition by ranolazine and molecular drug docking simulations to investigate the ranolazine binding site and binding characteristics. Results: Ranolazine acts as an inhibitor of TASK-1 potassium channels that inhibits TASK-1 currents with an IC50 of 30.6 ± 3.7 µM in mammalian cells and 198.4 ± 1.1 µM in X. laevis oocytes. TASK-1 inhibition by ranolazine is not frequency dependent but shows voltage dependency with a higher inhibitory potency at more depolarized membrane potentials. Ranolazine binds within the central cavity of the TASK-1 inner pore, at the bottom of the selectivity filter. Conclusions: In this study, we show that ranolazine inhibits TASK-1 channels. We suggest that inhibition of TASK-1 may contribute to the observed antiarrhythmic effects of Ranolazine. This puts forward ranolazine as a prototype drug for the treatment of atrial arrhythmia because of its combined efficacy on atrial electrophysiology and lower risk for ventricular side effects.